Technology integration and teachers’ competency in the development of 21st-century learning in EFL classroom - Nurhidayat, Eka; Mujiyanto, Januarius; Yuliasri, Issy; Hartono, Rudi (Intelektual Pustaka Media Utama, 2024)
This study examined the role of technology integration and teachers' professional competence in developing 21st-century learning. Present studies show a significant gap between technology integration and teachers’ competency in developing 21st-century learning. This study highlights the pivotal roles of technology integration and teacher competence in modern education. In an era where technology has transformed teaching and learning, understanding the synergy between these two factors is crucial for educational advancements. The study employs a descriptive quantitative approach. It seeks to understand the current state of technology integration and teacher competence by collecting data from in-service teachers within the English teacher's forum. The data collection methods encompass questionnaires and interviews to gain comprehensive insights into the subject matter. The research design of this study primarily relies on a descriptive approach, which involves the systematic collection and analysis of data to describe and understand the existing situation. The data-gathering process, through questionnaires and interviews, ensures a comprehensive exploration of the research questions. The results show that technology integration and teacher competency significantly influence the development of 21st-century learning.